Examining How Medical Staff Members Perceive How Emotions Affect Their Behavior When Interacting with Patients - Atef Eid Madkour Elsayed; Abdulrahman Omar Alfakhri; Yoused Mohammed Alhowaiti; Najah Almutairi; Raneem Ahmed Altalal; Fatema Mohsin Khamis; Ammar Ahmed Zamil; Mohammed Mohsin Khamis; Zainab Abdulkhaleq Mohamed Habib Mohamed; Norah Majed Albalawi; Rayan Khalid R Albalawi (Metallurgical and Materials Engineering, 2024)
Background: Emotions significantly influence physicians' behavior during patient interactions, yet their impact remains underexplored. Transient mood states (e.g., positive mood, fatigue, nervousness) and enduring emotional conditions such as burnout can shape clinical decisions and care quality. Burnout, defined as a response to chronic work stress, may further moderate these effects. This study investigates how medical staff perceive the role of emotions in their professional behavior and examines burnout as a moderating factor. Methods: The study recruited 150 physicians (56.7% male) from a major healthcare organization, including family physicians, pediatricians, and internists. Participants completed a validated questionnaire assessing mood states, burnout, and self-reported engagement in five patient-related behaviors: communication, prescribing, ordering lab tests, requesting diagnostic imaging, and specialist referrals. Burnout was measured using Kushnir and Melamed’s scale. A two-way repeated-measures ANOVA analyzed the effects of mood states and burnout levels on these behaviors. Results: Significant mood effects were observed across all five behaviors (p < 0.001), with positive moods enhancing communication (mean = 5.75) and negative moods, fatigue, and nervousness reducing it. Burnout significantly influenced behaviors such as ordering lab tests (p = 0.04), diagnostic imaging (p = 0.003), and specialist referrals (p = 0.02). Interaction effects between mood and burnout were significant for most behaviors, highlighting the complex interplay between these factors. For instance, high-burnout physicians exhibited increased diagnostic testing in negative emotional states. Conclusion: Emotions, both transient and enduring, shape physicians' professional behaviors, with burnout serving as a critical moderating factor. High burnout levels exacerbate the negative impact of adverse moods on patient interactions and decision-making. Interventions targeting emotional well-being and burnout in medical staff could improve communication, reduce errors, and enhance care quality. Further research should explore strategies to mitigate these effects in clinical settings.